PEMBUATAN BUKU REFERENSI KEMONO SEBAGAI UPAYA PENGENALAN ALIRAN SENI ANTHROPOMORFIS DENGAN MENGGUNAKAN KARAKTER TOKOH DALAM CERITA FABEL - Hafiidh, Rasyuqa Asyira; Bahruddin, Muh; Aziz, Abdul (Jurnal ArtNouveau, 2013)
From this rapid evolutions of cyber world appears many new cultures in art styles, one of them is an anthropomorphic art style. This art style is already widely recognizable in the rest of the world. But in Indonesia, it is not that well-known; most of them are only recognize this kind of art just as a fable or mascot. The goal of this project is to make a book that is specified about anthropomorphic arts that can give the target citizens knowledge in anthropomorphic arts using kemono. The design was done with a qualitative approach, namely observations, interviews, and focus group discussions in order to formulate a concept in the design process. From the analysis, it was found that the majority of anthropomorphic art fans around the world are mainly teenager to adulthood, and it was proven that kemono is a distinct anthropomorphic style from Japan. Also, it was decided to use Si Kancil as a chosen famous fable as an example. After going through the process of data analysis, found the keyword as a design concept which is